2013
DOI: 10.5051/jpis.2013.43.5.215
|View full text |Cite
|
Sign up to set email alerts
|

Determination of levels of nitric oxide in smoker and nonsmoker patients with chronic periodontitis

Abstract: PurposeCigarette smoking is a major risk factor in periodontal diseases. The pathogenesis of periodontal diseases may be affected by alterations of the inflammatory response by smoke. Nitric oxide (NO) is a gaseous, colorless, highly reactive, short-lived free radical with a pivotal role in the regulation of various physiological and pathological mechanisms in the body. It is important in host defense and homeostasis, on the one hand, whereas, on the other hand, it modulates the inflammatory response in period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…↑ NO p = 0.000 Positive correlation with PD Despite the fact that the Griess reaction was the most frequently used method in the methodology for determining the nitric oxide, these test results are very heterogeneous. Significantly higher salivary NO levels in the course of periodontitis, as in our assessment, were obtained in five other studies [6,25,26,28,29], and significantly decreased in two others [7,27]. These differences resulted from many reasons.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…↑ NO p = 0.000 Positive correlation with PD Despite the fact that the Griess reaction was the most frequently used method in the methodology for determining the nitric oxide, these test results are very heterogeneous. Significantly higher salivary NO levels in the course of periodontitis, as in our assessment, were obtained in five other studies [6,25,26,28,29], and significantly decreased in two others [7,27]. These differences resulted from many reasons.…”
Section: Discussionsupporting
confidence: 74%
“…Table 2 shows the test results on nitric oxide levels in GCF, saliva, and blood serum in periodontitis (the previous classification of periodontitis was used in tests. [6,7,[24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-described, yet puzzling and hitherto unproven, association between periodontal disease and CVD[280282] has been variably attributed to direct vascular entry of these largely nitrate-reducing oral pathogens[283286], generalized immune activation, systemic inflammation, and endothelial dysfunction, all processes that are improved with periodontal treatment (typically bactericidal chlorhexidine rinses with or without quadrant scaling)[193,287290]. Interestingly, both salivary nitrate and nitrite concentrations and gingival expression of NO-forming NOS have been found to be increased in periodontal disease, which also tend to increase with disease severity and improve with periodontal treatment[99,193,291,292]. However, it remains uncertain whether increased nitrite derives from oxidation of gingival NOS-derived NO or bacterial reduction of salivary nitrate.…”
Section: Dysbiosis Of the Microbiome In Pulmonary Hypertension And Vascmentioning
confidence: 99%
“…It may affect the synthesis of osteoblasts during maturation, and is an important marker for bone mineralization and activity of osteoblasts (23). Osteocalcin is secreted by osteoblasts during the matrix mineralization stage, and primarily facilitates bone mineralization (24). The present study demonstrated that nicotine inhibited AP and osteocalcin expression, thereby leading to injury to alveolar bone.…”
Section: Discussionmentioning
confidence: 50%